In the shadow of the Holocaust : Nazi persecution of Jewish-Christian Germans - Tent, James F. (Modern war studies, 2003)
Innocents in classrooms -- Mischlinge need not apply -- Drawing the line -- The penultimate step: forced labor -- A time of silence